Determinant of Firm Value LQ45 on Indonesia Stock Exchange - Mariana mariana (Syntax Corporation Indonesia, 2020)
This research aims to determine the profitability and leverage of partial influence on the firm value LQ45 on the Indonesian stock exchange in 2015-2019. The research method used is a double linear regression analysis with the help of the SPSS 25.00 application. The results showed that profitability with leverage influence the firm value LQ45 on the Indonesian Stock Exchange in 2015-2019.